Effects of hemodialysis, peritoneal dialysis, and renal transplantation on the quality of life of patients with end-stage renal disease - Zhang,Lijuan (2020)
SUMMARY OBJECTIVE: To evaluate the effects of hemodialysis, peritoneal dialysis, and renal transplantation on the quality of life of patients with end-stage renal disease (ESRD) and analyze the influencing factors. METHODS: A total of 162 ESRD patients who received maintenance hemodialysis, continuous ambulatory peritoneal dialysis, and renal transplantation from February 2017 to March 2018 in our hospital were divided into a hemodialysis group, a peritoneal dialysis group, and a renal transplantation group. The baseline clinical data, serum indices, as well as environmental factors such as education level, marital status, work, residential pattern, household income, and expenditure were recorded. The quality of life was assessed using the short-form 36-item (SF-36) scale reflecting the Physical Component Summary (PCS) and the Mental Component Summary (MCS). One-way analysis of variance and logistic stepwise multiple regression analysis were performed to analyze the factors influencing the quality of life. RESULTS: The renal transplantation group had the highest average scores for all dimensions of the SF-36 scale. The PCS and MCS scores of this group were higher than those of the hemodialysis and peritoneal dialysis groups. The peritoneal dialysis group had higher scores for physical functioning, physical role, bodily pain, general health, mental health, PCS, and MCS than those of the hemodialysis group. Age, HGB, GLU, and ALP were the main factors influencing PCS. Age, education level, residential pattern, medication expenditure, and monthly per capita income mainly affected MCS. CONCLUSION: In terms of quality of life, renal transplantation is superior to peritoneal dialysis and hemodialysis.